The utility of virtual reality and augmented reality in spine surgery - Yoo, Joon S.; Patel, Dillon S.; Hrynewycz, Nadia M.; Brundage, Thomas S.; Singh, Kern (Annals of Translational Medicine; Vol 7, Supplement 5 (September 10, 2019): Annals of Translational Medicine (Focus on: “Current Trends and Advancements in Spine Surgery”), 2019)
As the number of advances in surgical techniques increases, it becomes increasingly important to assess and research the technology regarding spine surgery techniques in order to increase surgical accuracy, decrease overall length of surgery, and minimize overall radiation exposure. Currently, augmented reality and virtual reality have shown promising results in regard to their applicability beyond their current functions. At present, VR has been generally applied to a teaching and preparatory role, while AR has been utilized in surgical settings. As such, the following review attempts to provide an overview of both virtual reality and augmented reality, followed by a discussion of their current applications and future direction.